(untitled) (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2024)
This research was carried out to determine the effectiveness of using Cognitive Behavior Therapy (CBT) in reducing academic anxiety and influencing academic procrastination in final-year students who are working on their thesis. This research method uses a single-case experimental design to test differences in participant behavior before and after providing intervention using this counseling technique. The participant was a student majoring in psychology who was working on a thesis and had symptoms of academic anxiety. Data collection using the academic anxiety scale by Utama (2015) with a reliability of 0.859 shows that academic anxiety is in the high category with a score of 90. However, after being given intervention through cognitive behavioral counseling techniques consisting of five sessions, academic anxiety decreased and was in the medium category with a score of 64. It was concluded that cognitive behavioral therapy techniques were effective in reducing the level of academic anxiety that affected students’ when completing their final assignment.